Investigation and response to a type 3 vaccine-derived poliovirus detected in an infant with hand, foot, and mouth disease — Guangdong, China, 2023 - Jialing Li; Lance E. Rodewald; Wei Zhang; Jian Liang; Xiaoping Shao; Qi Zhu; Jun Liu; Limei Sun; Jianfeng He (Journal of Health, Population and Nutrition)
Abstract Background The detection of type 3 vaccine-derived poliovirus (VDPV3) in an immunocompetent infant with hand, foot, and mouth disease (HFMD) raised concerns about potential transmission. This study aimed to investigate the risk of VDPV3 spread through comprehensive clinical, environmental, and epidemiological assessments. Existing literature highlights the rare emergence of VDPV3 in similar settings, emphasizing the need for robust surveillance and rapid response to prevent outbreaks. Case presentation Stool specimen from an 8-month-old female infant presented with HFMD without paralysis or immunodeficiency was tested positive for VDPV3 with 12 nucleotide changes in Foshan City. The infant had received routine vaccinations before and was otherwise healthy. No additional VDPV3 was detected in her follow-up samples, and the child fully recovered without complications. Measures A team was formed to investigate and respond in accordance with China’s National Health Commission and World Health Organization guidelines. Investigation included obtaining stool specimens from the child, her contacts, and local healthy children to test for evidence of poliovirus; conducting enhanced environmental surveillance for VDPV3 in wastewater; measuring vaccination coverage; searching hospitals and communities for unreported acute flaccid paralysis (AFP) cases; and evaluating the index infant for immunodeficiency. Results No additional VDPV3s were detected in stool samples from the index infant, her contacts, or local healthy children. Similarly, no VDPV3s were identified in wastewater samples. The child’s immune function was found to be normal. Historical vaccination coverage data revealed that Foshan had a high polio vaccination rate. An active search for AFP cases yielded no results. Over a period of more than one year, enhanced AFP surveillance and environmental surveillance were implemented, and no additional VDPV3s were detected during this time. Conclusions Based on Foshan’s high polio vaccine coverage rate, sensitive AFP case reporting system, and findings from the investigation, risk of transmission of VDPVs in the area was determined to be extremely low. No vaccination response was conducted. After one year of environmental and AFP surveillance, no further VDPV3s were detected, indicating cessation of transmission.